Sir Pete the Brave - Dean, James 1957- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2016)
When a dragon kidnaps Lady Callie, Sir Pete the Brave must come to her rescue.
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Pete, -- the Cat (Fictitious character) -- Fiction; Cats -- Juvenile fiction; Knights and knighthood -- Juvenile fiction; Dragons -- Juvenile fiction; Cats -- Fiction; Knights and knighthood -- Fiction; Dragons -- Fiction